THE DIFFICULTIES OF WRITING SCIENTIFIC WORK AT THE ENGLISH EDUCATION STUDENTS - Rizkariani Sulaiman; M. Muhajir (Journal of English Education, 2019)
The purpose of this study was to determine the students’ difficulties in writing scientific papers at the English Language Education, Universitas Muslim Indonesia and to find out the needs and learning objectives of the students. The sample was consisted of 44 English Education students registered at the UMI Faculty of Literature during the 2018/2019 academic year. To examine this problem, the study was conducted in a descriptive quantitative design. The instrument used in this study was questionnaires. Research questions consist of: 1) what are the difficulties faced by English Education major students in academic / scientific writing? 2) what are the common errors of English Education students in writing scientific papers? 3) what teaching approach can facilitate success in scientific writing? Based on the results of the study, the difficulties faced in the process of writing scientific papers were related to aspects of grammar (31%), scientific writing style / rules (24%), vocabulary, spelling and coherence (11%), writing arrangement (7%) and punctuation (5%); Three common errors that occur in writing scientific papers namely spelling (29.2%), use of capital letters (17, 75%), and punctuation (15.27%). The approaches needed by the teachers to strengthen and help students to improve their scientific writing referred to reviewing writing such as the level of words, sentences, paragraphs, and grammar, making outlines, applying three steps in the writing process such as planning, writing and revision, and understanding the formal and informal styles as well as oral and written forms so as to be able to avoid words and phrases that were not needed.